Prognostic values of adiponectin and leptin in assessment of osteoarthritis in menopausal HIV women in Nauth Nnewi Nigeria - Kalu, Ofia A.; Ukibe, Nkiruka R.; Ihim, Augustine C.; Okwara, John E.; Egwuatu, Perpetua A.; Ukibe, Gloria E.; Ukibe, Blessing C. (International Journal of Research in Medical Sciences, 2023)
Background: Human immune deficiency virus (HIV) has progressively been implicated with development of inflammatory disease including osteoarthritis. This study evaluated serum levels of adiponectin and leptin in women living with HIV with/without osteoarthritis who have been placed on highly active anti-retroviral therapy (HAART) in NAUTH, Nnewi, Nigeria. Methods: Eighty eight participants aged between 18 and 65 years attending HAART unit of NAUTH, Nnewi were randomly selected and grouped thus: Group A (premenopausal HIV seropositive women with osteoarthritis), group B (postmenopausal HIV seropositive women with osteoarthritis), group C (premenopausal HIV seropositive women) and group D (postmenopausal HIV seropositive women). Five milliliters of blood sample collected from each of participants for determination of adiponectin and leptin using enzyme linked immunosorbent assay (ELISA) technique. Results: Adiponectin level was significantly higher in postmenopausal HIV seropositive women with osteoarthritis compared with pre and postmenopausal HIV seropositive women without osteoarthritis (p<0.05 respectively). Similarly, leptin level was significantly higher in pre and post-menopausal HIV seropositive women with osteoartritis compared with their counterparts without osteoarthritis (p<0.05 respectively). A positive significant correlation was observed between Leptin and age in premenopausal HIV seropositive women with osteoarthritis. Also, a significant negative correlation was observed between adiponectin, age in pre and postmenopausal HIV seropositive women without osteoarthritis. Conclusions: The significant increases in adiponectin and leptin levels in pre and postmenopausal HIV seropositive women can be linked to severe inflammatory reaction due to osteoarthritis which might have been aggravated by combined effects of menopause and HIV infection.